A system dynamics model application to operating room planning and management. Issue 1 (2nd January 2023) - Faeghi, Shiva; Lennerts, Kunibert; Nickel, Stefan
ABSTRACT: Operating room (OR) management has remarkable impacts on the efficiency of not only OR departments themselves but also other functions of hospitals. Therefore, evaluation of long-term adequacy of specific decisions regarding the OR planning is of a notable importance. Since hospitals deal with a varying environment, every long-term analysis must investigate the hospital responsiveness to the relevant changes. For this purpose, the system dynamics (SD) approach can be very useful. Generally, SD models are not dependent on high-quality and can be applied to problems at strategic levels. Using a SD approach, this paper aims to consider OR departments as multi-product systems and study their dynamism. The proposed model is based on a mesoscopic approach, which represents the flow processes through piecewise constant rates. The proposed model is generic, modular and easy to extend and described by means of MATLAB/Simulink®. A real case study is considered to validate and demonstrate its usefulness.